Model Stres Kerja dan Dampaknya pada Produktivitas: Analisis Literatur - Asla Hanifah Putri; Nadia Rohimah; Amanda Elizafitriani; Netty Merdiaty (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
This study explores the model of work stress and its impact on productivity through a comprehensive systematic literature review approach. The objectives of the study are to analyze the complex dynamics of work stress, identify determinants, and explore effective intervention mechanisms to mitigate its negative impacts. The research methodology uses a qualitative approach with meta-synthesis techniques, conducting an in-depth analysis of ten leading scientific journals published between 2020-2024. The results of the study revealed that work stress is a multidimensional construct influenced by individual, organizational, and contextual factors, with key variables including workload, social support, organizational climate, and demographic characteristics. The findings indicate that work stress significantly affects psychological well-being and productivity, with different impacts based on gender, type of work, and organizational context. This study concludes the need for an integrative and proactive approach to work stress management, which does not only focus on individual interventions, but also transforms organizational structures and cultures.